Activation of Shigella flexneri type 3 secretion requires a host-induced conformational change to the translocon pore - Russo, Brian C. (PLoS Pathog, 2019)
Type 3 secretion systems (T3SSs) are conserved bacterial nanomachines that inject virulence proteins (effectors) into eukaryotic cells during infection. Due to their ability to inject heterologous proteins into human cells, these systems are being developed as therapeutic delivery devices. The T3SS assembles a translocon pore in the plasma membrane and then docks onto the pore. Docking activates effector secretion through the pore and into the host cytosol. Here, using Shigella flexneri, a model pathogen for the study of type 3 secretion, we determined the molecular mechanisms by which host intermediate filaments trigger docking and enable effector secretion. We show that the interaction of intermediate filaments with the translocon pore protein IpaC changed the pore’s conformation in a manner that was required for docking. Intermediate filaments repositioned residues of the Shigella pore protein IpaC that are located on the surface of the pore and in the pore channel. Restricting these conformational changes blocked docking in an intermediate filament-dependent manner. These data demonstrate that a host-induced conformational change to the pore enables T3SS docking and effector secretion, providing new mechanistic insight into the regulation of type 3 secretion.